Design & fabrication the front skirt of Proton Satria - Muhamad Farkhanif, Jamaluddin (2007)
This project present about front skirt of Proton Satria car. The objective this project is design and fabricates front skirt of Proton Satria car. Front skirts are fabricated using fiberglass as its raw material. The reason why front skirts are made out of fiberglass is because it is known for its lightness and it could stand shock or impact. When a car with an aerodynamic front skirt is speeding, the car will be stabilized by the front skirt because of its aerodynamic shape that produces downward force to the car therefore, the faster the car is the more stabilized it gets. The idea of fabricating front skirts for cars came because there's many product of this type already in the market. This makes it easier to find infonnation about how it is fabricated through the internet. The design of skirt that have curve shape can give aerodynamic properties such as that can reduce the air resistance when driving. Also, car looks nice and more speeding when using front skirt. Design three dimension the front skirt of Proton Satria is using solid work software. The result for first product is cannot successful because the mould polystyrene is inactive when touch resin. The result for second product is successful when use reused front skirt as a mould. The result for testing to assemble front skirt with Proton Satria model car is successful without problem. As conclusion, this project is successful followed by objective and scope.